Pengukuran Pengeluaran Energi pada Hari Kerja dan Hari Libur Menggunakan Aplikasi Smartphone pada Mahasiswa IPB - Jannah, Aisyah Fathul; Briawan, Dodik (Media Kesehatan Masyarakat Indonesia, 2018)
The effect of globalization made teenagers use health applications to achieve body fitness. The calories counter application is more practical and fast method to use. This study aimed to analyze energy expenditure in Bogor Agricultural University students with smartphone application compared with estimated energy expenditure using Physical Activity Level (PAL). The study design of this research was cross sectional study involving 61 students as samples. Physical activity data in a day were collected in two ways, using questionnaire and Samsung Health application. Energy expenditure was measured during weekday and weekend. Energy expenditure measured by Samsung Health application on weekday was 1130±719 kcal in male students and 634±195 kcal in female students meanwhile on weekend was 1124±659 kcal in male students and 679±232 kcal in female students. Energy expenditure measured by Samsung Health was smaller than energy expenditure measured by 1x24 hour physical activity record for both female and male students. The results can occur because not all activities can be measured in Samsung Health. The results of energy measurements with Samsung Health still need to be estimated through equations, especially in subjects with light intensity activities.